2012
DOI: 10.1007/s00395-012-0247-7
|View full text |Cite
|
Sign up to set email alerts
|

Proarrhythmia in a non-failing murine model of cardiac-specific Na+/Ca2+ exchanger overexpression: whole heart and cellular mechanisms

Abstract: The cardiac Na+/Ca2+ exchanger (NCX) generates an inward electrical current during SR-Ca2+ release, thus possibly promoting afterdepolarizations of the action potential (AP). We used transgenic mice 12.5 weeks or younger with cardiomyocyte-directed overexpression of NCX (NCX-Tg) to study the proarrhythmic potential and mechanisms of enhanced NCX activity. NCX-Tg exhibited normal echocardiographic left ventricular function and heart/body weight ratio, while the QT interval was prolonged in surface ECG recording… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 53 publications
6
44
2
Order By: Relevance
“…Indeed, this has been observed in homozygous knockout mice 16,25 and-conversely-a slowed inactivation was observed in homozygous overexpressor mice. 5,17 In our study, we also observed a trend toward accelerated I Ca inactivation in heterozygous KO mice, however, other than in homozygous KO mice, this trend did not reach statistical significance. One explanation may be that in homozygous KO mice, there is a complete NCX ablation, whereas in the heterozygous KO mice used in this study, NCX is only reduced to about half the normal expression level, thus resulting in a milder effect of NCX suppression on I Ca inactivation.…”
Section: Suppression Of Eads: Reduced Ap Duration and Interaction Of contrasting
confidence: 58%
See 3 more Smart Citations
“…Indeed, this has been observed in homozygous knockout mice 16,25 and-conversely-a slowed inactivation was observed in homozygous overexpressor mice. 5,17 In our study, we also observed a trend toward accelerated I Ca inactivation in heterozygous KO mice, however, other than in homozygous KO mice, this trend did not reach statistical significance. One explanation may be that in homozygous KO mice, there is a complete NCX ablation, whereas in the heterozygous KO mice used in this study, NCX is only reduced to about half the normal expression level, thus resulting in a milder effect of NCX suppression on I Ca inactivation.…”
Section: Suppression Of Eads: Reduced Ap Duration and Interaction Of contrasting
confidence: 58%
“…At the same time, if the amount of spontaneously released SR Ca 2+ is similar, NCX inactivation will be slower, that is, the period of NCX activity will be longer to extrude the same amount of Ca 2+ , a finding that has been demonstrated in previous studies. 5,[25][26][27] This would result in a DAD of smaller amplitude but longer duration as observed in this study ( Figure 5). Because the triggering of a spontaneous AP is an all or nothing response, it is the peak amplitude of a DAD and not the absolute number of DADs or the duration of the individual DAD that is crucial for the generation of sAPs.…”
Section: Ncx Knockout Suppresses Translation Of Dads Into Sapssupporting
confidence: 47%
See 2 more Smart Citations
“…These characteristics sharply limit the potential for I Ca L reactivation, yet numerous studies have observed EADs in the mouse 9-13 , and most have implicated I Ca L 11-14 . This presents a paradox regarding the electrophysiologic conditions required to elicit EADs in the mouse ventricle, which has important implications for interpreting arrhythmia mechanisms in a large number of disease models.…”
Section: Introductionmentioning
confidence: 99%